2014
DOI: 10.1073/pnas.1403409111
|View full text |Cite
|
Sign up to set email alerts
|

Deep classification of a large cryo-EM dataset defines the conformational landscape of the 26S proteasome

Abstract: The 26S proteasome is a 2.5 MDa molecular machine that executes the degradation of substrates of the ubiquitin-proteasome pathway. The molecular architecture of the 26S proteasome was recently established by cryo-EM approaches. For a detailed understanding of the sequence of events from the initial binding of polyubiquitylated substrates to the translocation into the proteolytic core complex, it is necessary to move beyond static structures and characterize the conformational landscape of the 26S proteasome. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
299
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(316 citation statements)
references
References 44 publications
17
299
0
Order By: Relevance
“…1C), indicating less structural heterogeneity. The overall structure differs notably from the reconstruction from 26S proteasomes alone, which predominantly adopt the s1 conformation (6), and appears more similar to the s2 conformation (13). Most importantly, two extra densities in the direct vicinity of Rpn1 are clearly distinguishable.…”
Section: Dmentioning
confidence: 72%
See 3 more Smart Citations
“…1C), indicating less structural heterogeneity. The overall structure differs notably from the reconstruction from 26S proteasomes alone, which predominantly adopt the s1 conformation (6), and appears more similar to the s2 conformation (13). Most importantly, two extra densities in the direct vicinity of Rpn1 are clearly distinguishable.…”
Section: Dmentioning
confidence: 72%
“…Previous analysis revealed that the conformational states of the RPs at the two CP ends are not correlated (6,13,15). Therefore, the following analysis was performed using the holocomplex cut into two halves (6, 13), i.e., the two RPs of the double-capped 26S proteasomes were treated as separate particles.…”
Section: Dmentioning
confidence: 99%
See 2 more Smart Citations
“…[26][27][28][29][30][31][32][33][34][35] This kind of information is also crucial for modeling the drug-receptor interactions 36 or for understanding the thermodynamics and kinetics of crystal growth processes 37,38 and, consequently, the polymorphism associated with pharmaceutical compounds. 25 Yet another reason for the conformational landscape analysis of a drug molecule is that it can suffer large structural changes during its functional cycle, 39 so that the conformation of the bioactive conformer could be significantly different from those of the most stable one in a particular solvent or in gas phase. 40 The conformational landscape of LEV in water and dichloromethane was studied previously by Li and Si 40 who identified 9 conformers.…”
Section: Introductionmentioning
confidence: 99%